Advantages of L-3-[(18)F] fluoro-alpha-methyl tyrosine over 2-[(18)F]-fluoro-2-deoxyglucose in detecting liver metastasis during positron emission tomography scan - Kodaira, Sayaka (Springerplus, 2016)
PURPOSE: We aimed to assess the usefulness of positron emission tomography (PET) using the amino acid tracer L-3-[18F] fluoro-alpha-methyl tyrosine (FAMT) in detecting metastatic liver lesions compared with 2-[18F]-fluoro-2-deoxyglucose (FDG). METHODS: We included 24 patients with liver metastases who underwent both FDG-PET/computed tomography (CT) and FAMT-PET/CT. Maximum standardized uptake value (SUVmax) and tumor-to-liver parenchymal (T/L) ratio were analyzed to evaluate the correlation between FDG and FAMT uptakes in metastatic liver lesions; adenocarcinoma (AC, n = 21), squamous cell carcinoma (SCC, n = 23), neuroendocrine tumor (NET, n = 9), and carcinoid tumor (CAR, n = 6). RESULTS: We detected 59 lesions on performing either FDG-PET or FAMT-PET. NETs had significantly lower T/L ratios for FAMT (median, 1.00; range, 0.86–1.34) compared with those for FDG (median 2.86; range 1.70–6.13, p < 0.01). CAR tumors tended to reveal lower T/L ratios for FDG (median 1.10; range 0.78–1.92) than those for FAMT (median 1.80; range 0.80–2.34). Comparison of T/L ratios of SCC and AC revealed that FAMT in the metastatic liver lesions of SCC was higher than those of AC (p < 0.05). CONCLUSION: FAMT-PET could detect metastatic liver lesions from various cancers, except NET.